2020
DOI: 10.1177/1060826520913264
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration into the Impact of Social Networking Site (SNS) Use on Body Image and Eating Behavior of Physically Active Men

Abstract: The rapid proliferation of social networking sites (SNSs) has transformed the way people now socialize and communicate. SNSs have been recognized to contribute to body image (BI) dissatisfaction and disordered eating behavior (EB). Few qualitative studies have explored this issue in men. The aim of the current study was to investigate male SNS use and possible impacts on BI and EB. One-to-one semi-structured interviews were conducted with eight men in the United Kingdom. Interviews aimed to examine men’s views… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 87 publications
3
2
0
Order By: Relevance
“…In their study, participants were influenced by peers, celebrities, and fitness models, mainly in a negative manner. Consistent with the findings of Flannery et al, 35 students in the present study generally framed online SM celebrities as negative influences on eating behaviours. Although participants saw high‐profile SM users as motivational, they also expressed concern around how others might compare themselves against unrealistic body standards, which could negatively impact food behaviours and body image.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In their study, participants were influenced by peers, celebrities, and fitness models, mainly in a negative manner. Consistent with the findings of Flannery et al, 35 students in the present study generally framed online SM celebrities as negative influences on eating behaviours. Although participants saw high‐profile SM users as motivational, they also expressed concern around how others might compare themselves against unrealistic body standards, which could negatively impact food behaviours and body image.…”
Section: Discussionsupporting
confidence: 92%
“…Students also reported that online connections can influence dietary behaviours of SM users. This theme aligns with research by Flannery et al, 35 who investigated the effects of SM use on body image and eating behaviours in physically active men. In their study, participants were influenced by peers, celebrities, and fitness models, mainly in a negative manner.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This correlation supported several deep-rooted sociocultural models that links media, parents, and peer to negatively impact body image & cause eating disorders [10]. Media has time and again targeted for depicting the ideal woman to be thin that further causes body image disturbances and wrong eating habits [11]. A few contradictory studies also say the pictures of lean women can have either a little or no effect on audiences but, the pictures of obese women had a good effect on women's body image [12].…”
Section: Introductionsupporting
confidence: 57%